2021
DOI: 10.1002/vms3.520
|View full text |Cite
|
Sign up to set email alerts
|

Faecal concentrations of ceftiofur metabolites in finisher pigs administered intramuscularly with ceftiofur

Abstract: The objective of this study was to determine the effects of dietary fibre level and source on faecal ceftiofur metabolites concentrations after intramuscular administration of therapeutic ceftiofur hydrochloride in finisher pigs. Pens of finisher pigs (n = 36), with an equal number of barrows and gilts, were randomly assigned to 1 of 3 dietary treatment groups: basal diet composed of corn grain and soy bean meal with no supplement and formulated to contain 8.7% neutral detergent fibre (NDF), supplemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Fecal microbiome largely represents the microbes present in the distal region of the hindgut, while other gut sections contain different microbial communities compared with that of the feces [ 88 , 89 ]; meanwhile, the fecal microbiome is considered an important source of ARGs for other animals in the pens and other farms [ 90 ]. While our study followed a single cohort of piglets from birth to market age in order to characterize the fecal microbiome and AMR, the study has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal microbiome largely represents the microbes present in the distal region of the hindgut, while other gut sections contain different microbial communities compared with that of the feces [ 88 , 89 ]; meanwhile, the fecal microbiome is considered an important source of ARGs for other animals in the pens and other farms [ 90 ]. While our study followed a single cohort of piglets from birth to market age in order to characterize the fecal microbiome and AMR, the study has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the ceftiofur group, all fecal samples of one female pig (pig n • 2) contained measurable amounts of ceftiofur-related residues, measured as desfuroylceftiofuracetamide (Figure 2). In a recently published study by Gaire (2021) on finisher pigs, ceftiofur-related residues could be detected in the feces of all treated pigs (n = 25), while in our study, the feces of only one out of eight pigs contained residues [23]. A possible explanation could be that the higher dose of ceftiofur received by the finisher pigs (4.4 mg•kg −1 BW vs. 3 mg•kg −1 BW) resulted in a higher concentration in the gut.…”
Section: Ceftiofur Ceftiofur-related Metabolites and Cefquinome: Inte...mentioning
confidence: 99%
“…The results showed that at the genus level, a difference was demonstrated between pigs from different breeds. The study by Gaire (2021) did not mention which breed the pigs belonged to. Interestingly, the concentrations of desfuroylceftiofuracetamide in the different gut segments of pig n • 2 were in the same range as in the other pigs, suggesting a slower degradation during gut transit.…”
Section: Ceftiofur Ceftiofur-related Metabolites and Cefquinome: Inte...mentioning
confidence: 99%
See 1 more Smart Citation